Assessment of liver stiffness measurement and ultrasound findings change during inotuzumab ozogamicin cycles for relapsed or refractory acute lymphoblastic leukemia. (30th December 2021) - Ravaioli, Federico; Marconi, Giovanni; Martinelli, Giovanni; Dajti, Elton; Sartor, Chiara; Abbenante, Maria Chiara; Alemanni, Luigina Vanessa; Nanni, Jacopo; Rossini, Benedetta; Parisi, Sarah; Colecchia, Luigi; Cristiano, Gianluca; et al.
Abstract: In adult patients, acute lymphoblastic leukemia (ALL) is a rare hematological cancer with a cure rate below 50% and frequent relapses. With traditional therapies, patients with relapsed or refractory (R/R) ALL have a survival that may be measured in months; in these patients, inotuzumab ozogamicin (IO) is an effective therapy. IO was linked to increased risk of veno‐occlusive disease/sinusoid obstruction syndrome (VOD/SOS), liver injury, and various grade of liver‐related complications during clinical trials and real‐life settings; however, hepatologic monitoring protocol is not established in this population. In our institution, 21 patients who received IO (median of 6 doses of IO administered) for R/R ALL were prospectively followed for hepatologic surveillance, including clinical evaluation, ultrasonography, and liver stiffness measurement (LSM) biochemistry. After a median follow‐up of 17.2 months, two SOS events were reported (both after allogeneic transplant) as IO potentially related clinically relevant adverse event. Mild alterations were reported in almost the totality of patients and moderate‐severe liver biochemical alterations in a quarter of patients. Within biochemicals value, AST and ALP showed an augment related to IO administration. LSM linearly augmented for each IO course administered. Baseline LSM was related to liver‐related changes, especially with the severity of portal hypertension (PH)‐related complications. Pre‐transplant LSM was higher in patients receiving IO when compared with a control cohort. PH‐related complications were discovered in nearly 77% of patients, with clinically significant PH occurrence and development of ascites in 38% and 14%, respectively. This prospective experience constitutes the rationale to design a hepatologic monitoring program in patients receiving IO. LSM may be of pivotal importance in this program, constituting a rapid and effective screening that quantitatively correlates with liver alterations. Abstract : Intensive longitudinal hepatologic monitoring detected subclinical signs of liver injury in leukemia patients treated with inotuzumab. Ultrasound and liver stiffness measurement can help diagnosing/monitoring portal hypertension‐related complications after inotuzumab therapy.